Research on the dynamic pressure influence and support engineering strategy of roadway group under multi section collaborative mining conditions - Yantao Zheng; Chao Zhao; Bingxi Jian; Yulin Chen; Song Shi; Xuanlin Li; Changwu Liu; Qingwei Bu; Tiejun Tao (Scientific Reports)
Abstract Multiple roadways have been excavated to form an underground production system, which is used for multi section collaborative mining of room pillar structures, achieving efficient mining of underground inclined and steeply inclined ore bodies; however, due to the combined influence of surrounding rock stress disturbance in the roadway group and lateral stress of the ore room, the dynamic pressure influence of roadway group is prominent in multi section collaborative mining. In this article, a combination of various research methods, such as engineering research, numerical simulation, theoretical analysis, and engineering practice, are adopted with the multi section collaborative mining roadway group in Xifeng Mine as the engineering background; the research work has been carried out on the impact of dynamic pressure manifestation on roadway groups under multi section collaborative mining conditions, the mechanism of dynamic pressure roadway failure and instability, roadway support control strategies, and the design of dynamic pressure roadway group support in Xifeng Mine. Research has shown that: (1) for multi section collaborative mining engineering conditions, a reasonable design of interlayer distance is the key to the surrounding rock stability of the dynamic pressure roadway group, which can reduce the dynamic pressure impact of each middle section roadway on each other, while meeting the mining technology level and efficiency requirements of the ore body; (2) the end of the ore vein mining roadway near the ore room is a key support reinforcement area, which increases the risk of instability of the surrounding rock due to strong mining induced pressure; the secondary support and reinforcement area is the intersection of the ore vein mining roadway and external roadway, as well as the roof of the ore vein external roadway and the side walls near the ore room, which are affected by the risk of shallow loose body collapse; (3) The layout of the roadway group causes uneven disturbance of the surrounding rock stress environment, changes the stable bearing state, and thus intensifies the damage; The mining of the ore room causes the surrounding stress field to be relieved, and the stress imbalance and disturbance of the roadway surrounding rock are more obvious, leading to an increase in the hidden danger of failure and instability; (4) A joint support scheme for dynamic pressure roadway group was proposed (active support with “anchor rod + steel mesh + surface spraying” during the layout stage of the roadway group + passive reinforcement support with “steel arch + metal mesh + surface spraying” during the ore drawing stage), and the on-site support effect was safe and stable.